1994
DOI: 10.1159/000236822
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salmeterol with Placebo in Mild Asthma: Effect on Peripheral Blood Phagocyte Function and Cytokine Levels

Abstract: β2-Adrenergic agonists are widely prescribed for the symptomatic relief of asthma, but are not thought to alter the underlying pathogenesis. However, it has been suggested that salmeterol, a new β-agonist with prolonged bronchodilatory action, may have anti-inflammatory properties. A double-blind crossover study of 4 weeks of inhaled salmeterol versus placebo was performed using a chemiluminescence assay to measure peripheral phagocyte function before and after each treatment period. Circulating cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Sullivan et al [29] reported an anti-inflammatory effect of oral theophylline in a double-blind place bo-controlled study on the inflammatory re sponse of the bronchial mucosa to allergen inhalation in 19 atopic asthmatic subjects. In contrast, no evidence was obtained to support a clinically significant anti-inflammatory ac tion of a P-agonist, salmeterol, in a double blind cross-over study of 4 weeks of inhaled salmeterol versus placebo [30], Gardiner et al [31] also reported that any significant anti inflammatory effect of regular salmeterol therapy on airway inflammation using bronchoalveolar lavage in asthmatic patients could not be obtained. But all the study patients were receiving regular inhaled corticosteroid therapy and albuterol for symptomatic relief, so it might be possible that the potential anti inflammatory effects of P-agonists have been masked by the treatment with these drugs.…”
Section: Discussionmentioning
confidence: 98%
“…Sullivan et al [29] reported an anti-inflammatory effect of oral theophylline in a double-blind place bo-controlled study on the inflammatory re sponse of the bronchial mucosa to allergen inhalation in 19 atopic asthmatic subjects. In contrast, no evidence was obtained to support a clinically significant anti-inflammatory ac tion of a P-agonist, salmeterol, in a double blind cross-over study of 4 weeks of inhaled salmeterol versus placebo [30], Gardiner et al [31] also reported that any significant anti inflammatory effect of regular salmeterol therapy on airway inflammation using bronchoalveolar lavage in asthmatic patients could not be obtained. But all the study patients were receiving regular inhaled corticosteroid therapy and albuterol for symptomatic relief, so it might be possible that the potential anti inflammatory effects of P-agonists have been masked by the treatment with these drugs.…”
Section: Discussionmentioning
confidence: 98%
“…Our observations concerning the increase in salmeterol efficacy at increased receptor levels indicate that this may lead to variation among individuals in the efficacy and potency of partial agonists to produce bronchodilatation when β 2 ‐adrenoceptor levels vary. The response of an individual may also vary depending on prior exposure to β 2 ‐adrenoceptor agonist and bronchoconstrictor stimuli (Cheung et al , 1992; Ramage et al , 1994; Bhagat et al , 1995), or to the existence of polymorphisms of the β 2 ‐adrenoceptor as described by Green et al (1996). Further, the effects of desensitization will vary considerably; that is, individuals with higher initial levels of β 2 ‐adrenoceptor would predictably show an apparent resistance to desensitization if receptor levels are sufficiently high and the desensitization does not appreciably alter the efficacy of weak partial agonists.…”
Section: Discussionmentioning
confidence: 99%
“…To be long‐acting, an agonist must persist at the site of action and not cause extensive receptor desensitization. There is no evidence from studies of bronchodilatation that chronic salmeterol treatment induces tolerance (desensitization) to its bronchodilating effects, although there is evidence that tolerance develops to its protective effects against a bronchoconstrictor stimulus (Cheung et al , 1992; Ramage et al , 1994; Bhagat et al , 1995). One of the primary actions of β 2 ‐adrenoceptor agonists in the relaxation of smooth muscle is the activation of adenylyl cyclase (Johnson et al , 1993), and the relaxant effects of salmeterol on airway smooth muscle are directly correlated with the activation of adenylyl cyclase and subsequent intracellular accumulation of adenosine 3′:5′‐cyclic monophosphate (cyclic AMP) (Ellis et al , 1995).…”
Section: Introductionmentioning
confidence: 99%